E-learning open seminar on "Human–centered artificial intelligence in education: From theory to practice" - Kotsidis, Konstantinos; Anastasiades, Panagiotes (International Journal of Educational Technology and Learning, 2025)
The study focus the impact of AI applications in education, focusing on improving education quality and enhancing teaching methods. The Laboratory of Advanced Learning Technologies in Lifelong and Distance Learning (EDIVEA) at the University of Crete implemented an ICT-based distance learning program titled "Human-centred AI in Education. The pedagogical dimension: From Theory to Practice," involving 1883 teachers from all education levels. The analysis showed that trainees effectively used the training material in their teaching practices, demonstrating its practical value and importance in distance learning. The study also highlighted the significance of support and communication between tutors and trainees in addressing pedagogical issues. The research underscores the critical role of anthropocentric training programs focused on teachers’ needs. The successful application of the training material in real teaching scenarios validates the program’s effectiveness. The findings suggest that well-designed, human-centered AI training programs can significantly enhance teaching practices. Ongoing support and communication between tutors and trainees are crucial for the successful implementation of distance learning programs.